2011
DOI: 10.1258/ijsa.2011.010442
|View full text |Cite
|
Sign up to set email alerts
|

Enrolment and programmatic trends and predictors of antiretroviral therapy initiation from President's Emergency Plan for AIDS Relief (PEPFAR)-supported public HIV care and treatment sites in rural Mozambique

Abstract: Many countries in sub-Saharan Africa have made antiretroviral therapy (ART) available in urban settings, but the progress of treatment expansion into rural Africa has been slower. We analysed routine data for patients enrolled in a rural HIV treatment programme in Zambézia Province, Mozambique (1 June 2006 through 30 March 2009). There were 12,218 patients who were ≥15 years old enrolled (69% women). Median age was 25 years for women and 31 years for men. Older age and higher level of education were strongly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 14 publications
3
34
0
Order By: Relevance
“…Second, because pregnant women are routinely screened for HIV during antenatal care, they are generally healthier than patients that seek HIV testing at VCT centers. Previous research has found lower CD4 count to be predictive of retention in care 68,11,2022,2527 , and the women from PMTCT testing centers in this study had a higher median CD4 count and lower WHO stage at enrollment compared to the VCT group. Furthermore, pregnant women who discover their HIV status through routine screening as part of antenatal care may be less prepared for the diagnosis than those who actively seek testing, which may impact subsequent HIV care 14 .…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Second, because pregnant women are routinely screened for HIV during antenatal care, they are generally healthier than patients that seek HIV testing at VCT centers. Previous research has found lower CD4 count to be predictive of retention in care 68,11,2022,2527 , and the women from PMTCT testing centers in this study had a higher median CD4 count and lower WHO stage at enrollment compared to the VCT group. Furthermore, pregnant women who discover their HIV status through routine screening as part of antenatal care may be less prepared for the diagnosis than those who actively seek testing, which may impact subsequent HIV care 14 .…”
Section: Discussionmentioning
confidence: 42%
“…The results of this study in 18 clinics is similar to a previous analysis from two clinics in the same region, which demonstrated that compared with those referred from VCT centers, patients referred from PMTCT centers were less likely to enroll at an ART clinic ≤30 days from HIV testing; were similarly likely to have a CD4 test done ≤30 days after ART clinic enrollment; and were less likely to initiate ART ≤90 of their CD4 test 5 . Another study in Mozambique found that ART-eligible women (including pregnant women) had a lower odds of initiating ART compared to men 20 . Two studies in South Africa also found that pregnant women had higher rates of LTFU after starting ART compared to non-pregnant subjects 11,21 .…”
Section: Discussionmentioning
confidence: 99%
“…29 The median Hb level was 9.9 g/dl in adults upon enrollment in HIV care in rural Zambézia Province, and Hb was <8.0 g/dl in 25% of TB/ HIV patients at ART initiation. 30,31 Malaria and intestinal helminthes are prevalent, and iron-deficiency anemia is thought to be common. [32][33][34] During Mozambique's initial response to the HIV epidemic, first-level health workers used a 2005 Mozambican guideline adapted from a standard World Health Organization guideline recommending that anemia (or pallor) be treated with presumptive iron supplementation, anthelminthics, and antimalarials.…”
Section: Introductionmentioning
confidence: 99%
“…This proportion declined over time, consistent with trends observed in HIV programmes in Mozambique, South Africa, Rwanda, and East Africa. 7,13,[15][16][17] These findings provide evidence for the effectiveness of our programme in reaching and enrolling HIV-infected individuals at earlier stages of disease. In addition, as the programme matured, the number of enrolled clients increased annually until 2012, possibly reflecting improved access to our services, and increased To compare the distribution of study characteristics for participants by year, we employ Kruskal-Wallis tests.…”
Section: Discussionmentioning
confidence: 95%